The stone witch of Florence [large type] - Rasche, Anna (Thorndike Press, a part of Gale, a Cengage Company, 2024)
"1348. As the Black Plague ravages Italy, Ginevra di Gasparo is summoned to Florence after nearly a decade of lonely exile. Ginevra has a gift--harnessing the hidden powers of gemstones, she can heal the sick. But when word spread of her unusual abilities, she was condemned as a witch and banished. Now the same men who expelled Ginevra are begging for her return. Ginevra obliges, assuming the city's leaders are finally ready to accept her unorthodox cures amid a pandemic. But upon arrival, she is tasked with a much different mission: she must use her collection of jewels to track down a ruthless thief who is ransacking Florence's churches for priceless relics--the city's only hope for protection. If she succeeds, she'll be a recognized physician and never accused of witchcraft again. But as her investigation progresses, Ginevra discovers she's merely a pawn in a much larger scheme than the one she's been hired to solve. And the dangerous men behind this conspiracy won't think twice about killing a stone witch to get what they want..."--Back cover.